"he who made the Lamb": Catechistic Subversion of Children's Literature in Blake's Songs. Issue 1 (April 2020) - Smith, David
Abstract : William Blake's Songs of Innocence and of Experience employed catechistic structures frequently found in eighteenth-century children's literature; however, this appropriation by Blake provokes questions about his political and aesthetic agenda. Children's literature, though increasingly popular throughout the eighteenth century, was not a vehicle for serious art and commentary. Likewise, catechisms, both in religious texts like the Book of Common Prayer and in children's books by writers like Bunyan, Isaac Watts, and Anna Laetitia Barbauld, supported religious and civil hierarchies that Blake rejected. Yet the participatory nature of catechesis provided Blake the opportunity to unveil his own political-aesthetic program for revolution and redemption. Through the contraries of image and word in "The Lamb" and "The Tyger" Blake encourages readers to participate in the creative process, to become artists. The catechistic poems celebrate children's connection to the imagination and attempt to reeducate adults from their indoctrinated obedience to Church and State.